Obiltoxaximab: Adding to the Treatment Arsenal for Bacillus anthracis Infection. (October 2017) - Hou, Audrey W.; Morrill, Amanda M.
Objective: To review the safety and efficacy of obiltoxaximab, a monoclonal antibody indicated for the treatment of Bacillus anthracis inhalational anthrax in adult and pediatric patients.Data Sources: A MEDLINE (1946 to May, week 1, 2017) and EMBASE (1980 to 2017, week 19) search was performed using the search terms obiltoxaximab OR ETI-204 OR Anthim AND anthrax .Study Selection and Data Extraction: All English-language clinical studies in both animal and human models assessing the safety and efficacy of obiltoxaximab were included.Data Synthesis: A total of 5 articles have been published on clinical studies examining safety and efficacy of obiltoxaximab. Efficacy studies in 2 animal models, New Zealand White rabbits and cynomolgus macaques, showed higher rates of survival post–anthrax exposure when obiltoxaximab was administered. Safety studies in healthy human volunteers showed that it was tolerated, with a relatively low incidence of adverse events.Conclusion: Based on these clinical studies and the implausibility of conducting a trial in infected individuals, obiltoxaximab is a safe and efficacious addition to the anthrax antitoxin armamentarium to protect against and treat inhalational anthrax.